Henoch-Schönlein purpura in adulthood: Henoch-Schönleinova purpura pri odraslem - Skačej, Helena; Holc, Iztok; Pahor, Artur (Acta Medico-Biotechnica, 2021)
Background: Henoch-Schönlein purpura (HSP) is a systemic inflammation of small-vessel walls that predominantly affects children. In adults, on the other hand, it appears rarely, and can be more severe. The disease is characterised by a tetrad of clinical signs which manifest the skin, joint, gastrointestinal, and kidney involvement. HSP is diagnosed using internationally-accepted criteria. At present, there is no effective specific therapy for children and adults. However, in cases of severe organ involvement, aggressive treatment may stabilise the disease. Case report: We present a case of a 59-year-old immunologically uncompromised patient with an extremely severe form of HSP. Epidemiology, etiopathogenesis, clinical features, diagnostic procedures, differential diagnosis, treatment, and prognosis of the disease are discussed. Conclusions: The patient was treated with corticosteroids, human polyspecific immunoglobulins, and immunosuppressive agents. A satisfactory clinical remission has been achieved.